Noise, Regression Dilution Bias, and Solar-Wind/Magnetosphere Coupling Studies - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2022)
Using numerical experiments, the effects of noise in the solar-wind and magnetospheric data on fits to the data are examined. In particular, the impact of noise amplitude on the functional forms of best-fit solar-wind driver functions is explored. The presence of noise (measurement error) will make it difficult to use solar wind and magnetosphere data to uncover (or confirm) the formula that describes the physics of the driving of the magnetosphere.